Integrated Management of Childhood Illness Guideline Application at Primary Healthcare Centers in Al Hillah City - Muhaisen , Ali Sakran; Al Mayahi, Naji Yasser; Baiee , Hasan Alwan (International Journal of Psychosocial Rehabilitation, 2020)
Integrated Management of Childhood Illness is a guideline developed by the 'World Health Organization' during the last two decades to reduce the mortality and morbidity of under five years children in order to achieve the millennium development goal. Studies on this issue are very scarce in IraqTo evaluate the capacity in the application of IMCI of Iraqi primary health care providers and to identify the main barriers facing them during their daily activities.This was a cross-sectional study conducted on a convenient sample of (130) health providers working in Integrated Management of Childhood program, the sample was selected randomly from (8) primary health care centers in Al Hilla City-Babylon province-Iraq. The duration of the study started from November 2019 through February 2020 .A pretested semi-structured questionnaire was adopted from (WHO) technical documents and was used to interview and checking the performance of the participating health care providers enrolled in this study after obtaining their verbal consents.The questionnaire includes questions about demographic characteristics of health care workers and the regular activities that the health worker should do to provide proper care for under-five children who attended primary health care centers.Our findings showed that performance of about (60%) the staff was poor , about (27%) had fair practice while of them (13%) had good practice. About one fifth (21.5%) check child temperature,( 47%)used to measure the body weight, ( 46.2%) were asking regarding cough or respiratory problems,(49.2%) asked for diarrhea, (31.5%) were asking for fever,(30.8 %) were assessing ear problems,only(18.5 % ) were seeking palm pallor,( 70.7%) asked about breastfeeding,(33.8%). About three quarter of health care workers (73%) had not trained in this field. The findings of this study identified that one of the main barrier of applying this approach was the time pressure due to patients overloadThis study showed that the majority of healthcare personnel had poor Practical